Fragmentação socioespacial, práticas espaciais e cotidiano: bairro Residencial Integração - Uberlândia (MG) - Amorim, Paulo Henrique Silva de (2022)
In an attempt to understand the unequal production of urban space and taking into account its objectives and subjectives dimensions, the present work aimed to analyze, from the sociospatial formation, the Residencial Integração district, located in the East Sector of Uberlândia (MG). To meet the main objective of the work, daily life was taken as an analytical component, conditioned to the spatial practices of the interviewed citizens, was taken as an analytical object, as a method of expressing peculiar forms of resistance, integration and differentiation that lead to the process of sociospatial fragmentation. For this, the socio-spatial fragmentation process was analyzed from five empirical dimensions (habitat, work, mobility, leisure and consumption), which, despite being interdependent, also carry variant overlaps according to the reach of possibilities that a city dweller has about the urban space. The methodological procedures that guided the scientific investigation were: 1) literature review; 2) field research; 3) semi-structured interviews; 4) identification of public transport lines and itinerary that circulate over the district; 5) identification of the main commercial and service infrastructures that serve the residents of Residencial Integração. After conducting 10 interviews and observations made during field research, the work revealed that the fragmentation of urban life faced by residents of Residencial Integração was based on various scales of daily life involving: 1) access to housing, when the neighborhood it was not yet recognized by the municipal town hall; 2) the absence of basic infrastructure for the maintenance of urbanity, which extends from the lack of green areas, squares and banking services, to the reduced offer of public transport service to city dwellers; 3) the segmentation of access to the city while a right, in view of the socioeconomic inequity that a large majority face, culminating in challenges to the point of not feeling belonging to the city that, in theory, they are part of Finally, we emphasize that the reading of the socio-spatial fragmentation process was carried out taking as an analytical object a reduced number of city dwellers, which, roughly speaking, can reveal distortions in the continuity of the research or even an accentuation of the segmentation of everyday life faced by these citizens.